2017
DOI: 10.2217/fon-2017-0281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Preoperative Liver Stiffness Measurements in Primary HBV-Positive Hepatocellular Carcinoma

Abstract: Aim: To analyze clinical significance of preoperative liver stiffness measurement (LSM) by FibroScan in postcurative resection hepatitis B virus (HBV) related hepatocellular carcinoma (HCC). Patients & methods:A total of 263 patients underwent preoperative LSM and curative operation for primary HBV-positive HCC were enrolled. The correlation between preoperative LSM and survival was analyzed. Results: All patients were stratified into two groups using the optimal cut-off value (13.2 kPa) of LSM using the recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The diagnostic and prognostic values of LSM by 2D-SWE for liver fibrosis of patients with chronic HBV infection have been extensively evaluated and validated ( 38 - 40 ), For patients with HBV positive HCCs, the presence of liver fibrosis is a well-known risk factor for both the development of post-treatment liver failure and prognosis ( 15 , 41 ). Therefore, considering the results of previous studies and current study, it is possible that the poorer survival of HCCs following RFA in patients with a higher LSM value could be partly due to the presence of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic and prognostic values of LSM by 2D-SWE for liver fibrosis of patients with chronic HBV infection have been extensively evaluated and validated ( 38 - 40 ), For patients with HBV positive HCCs, the presence of liver fibrosis is a well-known risk factor for both the development of post-treatment liver failure and prognosis ( 15 , 41 ). Therefore, considering the results of previous studies and current study, it is possible that the poorer survival of HCCs following RFA in patients with a higher LSM value could be partly due to the presence of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, accurately quantitative evaluation of the fibrosis is curial for evaluating prognosis and furtherly guiding satisfaction of HCC patients. Moreover, stratification of patients according to biomarkers is crucial for individualized treatment and prognostic prediction, such as Child–Pugh score and Model for end-stage liver disease (MELD) score ( 14 , 15 ). However, in clinical, liver fibrosis mainly is assessed through liver biopsy or postoperative historical examination, which is characterized by invasive, risk of complications and diagnostic bias ( 16 - 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…LSM by MRE as a parameter of preoperative and postoperative prediction models for ER indicated a good predictive performance and served as an independent predictor of LR in HBV-related hepatocellular carcinoma patients ( 107 ). A study enrolling 263 patients with HBV-related HCC who underwent curative resection suggested that preoperative LSM ≥13.2 kPa was an independent risk factor causing worse OS and RFS ( 108 ). Another prospective study measured HCC tumor stiffness (TS) measured by MRE in patients with HBV infection before hepatectomy (median:6 days, range:1-30 days) suggested that TS and vascular invasion were risk factors of HCC ER analyzed by the multivariate Cox proportional hazard model ( 109 ).…”
Section: Imaging Predictorsmentioning
confidence: 99%